2004
DOI: 10.1210/en.2003-0706
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Regulation of the Two Atrial Natriuretic Peptide Receptors in Testis

Abstract: By interacting with a guanylyl cyclase (GC) activity-containing receptor, termed GC-A, atrial natriuretic peptide (ANP) acts as a regulator of blood pressure and fluid volume homeostasis. High expression levels of GC-A in the testis and reported effects of ANP on testosterone secretion by Leydig cells are indicative of important local functions in this organ. Here we show, based on radioligand receptor labeling and immunological approaches, that seminiferous tubules rather than Leydig cells are the predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 42 publications
0
28
1
Order By: Relevance
“…Recent studies have also shown that the effects of ANP on the endothelial TJ barrier function are also mediated via changes in the phosphorylation status of occludin and ZO-1 at the TJ site (16). More important, NPR-A (or GC-B, the receptor of ANP) was recently shown to be predominantly localized in the seminiferous tubule instead of cells in the interstitium, such as Leydig cells in rat testes (43). Different natriuretic peptides can exert differential effects on endothelial barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that the effects of ANP on the endothelial TJ barrier function are also mediated via changes in the phosphorylation status of occludin and ZO-1 at the TJ site (16). More important, NPR-A (or GC-B, the receptor of ANP) was recently shown to be predominantly localized in the seminiferous tubule instead of cells in the interstitium, such as Leydig cells in rat testes (43). Different natriuretic peptides can exert differential effects on endothelial barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figs 1 and 3, the mRNA expression of mGC-G is broadly in agreement with its protein expression in sperm from round spermatids to mature sperm. In a recent study, GC-A was shown to be expressed in round and elongated spermatids in the rat testis by radioligand receptor labeling and immunological approaches; however, its expression in cauda epididymal sperm was not reported (29). Although the sea urchin sperm-receptor GC localizes to the entire length of the flagellum (30), we found that mGC-G is restricted to the midpiece of the flagellum and the head region.…”
Section: Discussionmentioning
confidence: 54%
“…These data, demonstrating complex contraction and relaxation activities, are indicative of a major physiological role of guanylate cyclase/cGMP pathway in the regulation of tunica albuginea function related to testicular sperm transport (Middendorff et al, 2002). In addition to its role in the tunica albuginea, ANP was found to affect spermatogenesis during postnatal development (Muller et al, 2004). In fact, a male germ specific cGK-anchoring protein, designed as GKAP42 (Yuasa et al, 2000) is expressed in a stage-dependent manner in spermatocytes and round spermatids.…”
Section: Hydrolysis Of C-gmp In Tunica Albuginea Lamina Propria Permentioning
confidence: 85%
“…Thus growth regulation appears to represent an important aspect of the natriuretic peptide system (Silberbach & Roberts, 2001;Cameron & Ellmers, 2003). Considering that human spermatozoa can respond in a cGMP-dependent manner to ANP (Anderson et al, 1995) and that this peptide is capable of inducing acrosome reactions in spermatozoa (Rotem et al, 1998), there may be a probability for a role of GC-A in the regulation of the spermatozoal function (Muller et al, 2004).…”
Section: Hydrolysis Of C-gmp In Tunica Albuginea Lamina Propria Permentioning
confidence: 99%